Singgihan Pada Upacara Ngusabha Sambah Di Pura Bale Agung Desa Pakraman Subaya, Kecamatan Kintamani, Kabupaten Bangli - I Nengah Adi Widana; Ketut Sumadi; I Wayan Mandra (Kamaya: Jurnal Ilmu Agama, 2018)
The Balinese language as part of the Nusantara language can be said to have a long history of growth. Balinese language development has taken place during the Anak Wungsu Reign, marked with ancient Balinese inscriptions in copy with Old Javanese. One of the evidences of Balinese language development can be seen in the literary results (Balinese literature). Balinese literature is closely related to Hinduism and always supports one another. Balinese case is grouped according to the three perspectives that is according to its development, according to its form, and according to the way of narrative. The results of this research are (1) the factor of using singgihan at Ngusabha Sambah ceremony that is (a) myth of Ratu Ayu Alit Tegeh Pengubengan, (b) preserving tradition owned by ancestors, (c) geographical location of Village which is in hilly area and difficult to find means of entertainment, (d) self-maturation especially in the younger generation. (2) Shape singgihan at Ngusabha Sambah ceremony that is physical form (a) inspiration of poetry, (b) diction, (c) imagination, (d) concrete words, (e) figurative language, and (f) verification. And the inner form of composition consists of (a) theme or meaning, (b) feeling, c) tone, and (d) intention). (3) The implications of the sumpihan at the Ngusabha ceremony add to the use of the Balinese language that is a) Developing a Balinese language attitude, b) Increasing the love and care of the Balinese language as a mother tongue. c) Increasing the variety of Balinese vocabulary, d) Singgihan means to strengthen Sradha and Bhakti.